Comprehensive driving behavior model for intelligent transportation systems - Kamal, M. A. S.; Khan, Md. Raisuddin; Wahyudi, Martono; Muhida, Riza (2008)
This paper presents a novel approach of modeling human driving behavior in a more realistic way that can be effectively utilized in realizing intelligent transportation systems to ensure efficient, safe, secure and human-friendly vehicle control and transportations. A number of supporting systems based on individual driving behavior are identified. The proposed comprehensive driving model approximates complete behavior of individual drivers focusing not only the ideal steady and transient driving styles but also their natural variations. Simulation results and observations from real driving scenario illustrate the significance of the proposed model and its scopes.